Civil rights in the shadow of slavery the constitution, common law, and the Civil Rights Act of 1866 - Rutherglen, George (Oxford : Oxford University Press, 2013)
The author begins with the birth of civil rights - the circumstances, acts and legacy of the 39th Congress, constitutional origins, passage and structure of the Act, moves through the Fourteenth Amendment and into restrictive interpretations and quiescent years, and finishes with a chapter on discerning the future from the past and the contemporary significance of the Act.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Includes index.
Keywords: United States; African Americans -- Civil rights -- History; Reconstruction (U.S. history, 1865-1877)